2020
DOI: 10.3390/ijms21144916
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Infusion Leads to Aortic Dissection in LRP8 Deficient Mice

Abstract: Myeloid cells are crucial for the development of vascular inflammation. Low-density lipoprotein receptor-related protein 8 (LRP8) or Apolipoprotein E receptor 2 (ApoER2), is expressed by macrophages, endothelial cells and platelets and has been implicated in the development of cardiovascular diseases. Our aim was to evaluate the role of LRP8, in particular from immune cells, in the development of vascular inflammation. Methods. LRP8+/+ and LRP8−/− mice (on B6;129S background) were infused with angiotensin II (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Angiotensin II contributes to the contraction of human airway smooth muscle and induces AD in mice. 29 , 30 To further study the role of circ_0022920 , HASMCs were treated with angiotensin II to establish an in vitro cell model for AD. We found that circ_0022920 was significantly downregulated in angiotensin II‐treated HASMCs (Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Angiotensin II contributes to the contraction of human airway smooth muscle and induces AD in mice. 29 , 30 To further study the role of circ_0022920 , HASMCs were treated with angiotensin II to establish an in vitro cell model for AD. We found that circ_0022920 was significantly downregulated in angiotensin II‐treated HASMCs (Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Ang-II is a critical factor at the systemic and cellular level for the pathogenesis of vascular diseases in general ( Berk et al, 2000 ) and, in particular, for aortic diseases like aortic dissection and aneurysms ( Lagrange et al, 2020 ; Wu et al, 2021 ). Experimental work suggests that Ang-II in conjunction with RAGE (receptor for advanced glycation end products) increases phospho-VEC tyrosine-731 and VEC disruption that correlate with the induction of hyperpermeability of HUVECs and murine aortas ( Jeong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activated monocytes and platelet receptor glycoprotein Ib alpha (GPIbα) participate in local thrombin amplification through coagulation factor XI (FXI), thereby promoting the development of vascular inflammation and hypertension and accelerating the progression of AD [40]. Additionally, low-density lipoprotein receptor-related protein 8 (LRP8) is released from monocytes and can induce vascular inflammation and endothelial dysfunction, leading to AD [41].…”
Section: Monocytesmentioning
confidence: 99%